Detection and Analysis on Mutual Interference of Cathodic Protection Systems of Parallel Oil and Gas Pipelines in Southwest Mountainous Area - WANG Ai-ling, XIAN Guo-dong, YU Dong-liang, ZHAO Xiong, HUANG Wen, HU Shao-lei, CHEN Cheng (Cailiao Baohu, 2021)
The geological conditions of buried pipelines in southwest mountainous areas are complicated, the operation difficulty coefficient is large, the soil properties vary, and the corrosion is generally serious.Due to the restrictive routing of pipelines in mountain, the crude oil pipelines, gas pipelines and product oil pipelines are laid in parallel in the same pipeline corridor.The minimum separation distance is less than 1.5 meters.The parallel mode is laying in the same trench and laying in the same route.The independent cathodic protection system is used for each pipeline.In response to this situation, 5 stations and 14 valve rooms along the parallel pipelines in the southwest mountainous area were detected.It was found that cathodic protection in the station area had great impact on the parallel pipeline cathodic protection systems, interference between the oil and gas combined station and the valve cathodic protection system of the valve room is common.However, the range of mutual interference of parallel pipelines was limited, usually about 3 km away from the cathodic protection systems the change of the on-potential caused by the interference was less than 50 mV.